Combination Antibiotic Treatment of Serious Methicillin-Resistant Staphylococcus aureus Infections - Davis, J. S.; van Hal, S.; Tong, S. Y. C. (Seminars in Respiratory and Critical Care Medicine, 2015)
Outcomes from methicillin-resistant Staphylococcus aureus (MRSA) infections are relatively poor, at least in part due to the limitations of vancomycin (the current standard treatment for MRSA). Combination antibiotic treatment for MRSA infections is an attractive alternative as it could address most of vancomycin's shortcomings, including poor tissue penetration, slow bacterial killing, and emerging resistance in some strains of MRSA. However, the theoretical promise of combination therapy for MRSA infections has not been borne out in most in vitro and animal studies. Multiple combinations have been tested and have been either antagonistic, indifferent, or have had conflicting findings in various studies. This includes combinations of two primarily active agents (such as vancomycin plus daptomycin or linezolid), or the addition of gentamicin or rifampin to either vancomycin or daptomycin. However, hope on this front has come from an unexpected quarter. Although MRSA is by definition inherently resistant to nearly all β-lactam antibiotics, this class of drugs has consistently shown evidence of synergy with either daptomycin or vancomycin in over 25 separate in vitro studies, and a limited number of animal and human observational studies. However, there are currently insufficient data to recommend β-lactam combination therapy in routine clinical use. Results of current and planned randomized controlled trials of this strategy are awaited.
Keywords: methicillin-resistant Staphylococcus aureus; combination antibiotic therapy; vancomycin; daptomycin